Reinfection With the Hepatitis C Virus in Men Who Have Sex With Men After Successful Treatment With Direct-acting Antivirals in Germany: Current Incidence Rates, Compared With Rates During the Interferon Era. (28th September 2019) - Ingiliz, Patrick; Wehmeyer, Malte H; Boesecke, Christoph; Schulze Zur Wiesch, Julian; Schewe, Knud; Lutz, Thomas; Baumgarten, Axel; Simon, Karl-Georg; Hueppe, Dietrich; Rockstroh, Juergen K; Mauss, Stefan; Christensen, Stefan; et al.
Abstract: Background: Micro-elimination of the hepatitis C virus (HCV) includes treatment in populations at risk of ongoing HCV transmission, such as men who have sex with men (MSM) or people who inject drugs (PWID). We analyzed the HCV reinfection incidence rates of participants in the German hepatitis C cohort (GECCO) and compared our data to previous findings from the interferon era. Methods: Patients with HCV reinfections in the multi-centric GECCO cohort were compared to patients in whom no reinfection occurred. The HCV reinfection incidence rate in MSM was also compared to the incidence rate in the interferon era (using data from the European Acquired Immunodeficiency Syndrome Treatment Network [NEAT]). Results: Between January 2014 and April 2018, 48 HCV reinfections occurred in 2298 individuals (2%), with 2346 cured HCV episodes. The median time to reinfection was 500 days (range 16–1160) and the overall HCV reinfection incidence rate was 1.89 per 100 person-years (py; 95% confidence interval [CI], 1.41–2.48). In a multivariate analysis, the transmission risk in MSM was the only independent risk factor of HCV reinfection (odds ratio, 39.3; 95% CI, 4.57–334.40; P = .001). The incidence rate in MSM was 9.02 (95% CI, 6.48–12.26) per 100 py, compared to 1.14 per 100 py in PWID (95% CI, .56–2.09). The incidence rate for a first HCV reinfection in MSM was similar in the direct-acting antiviral era, compared to the interferon era, with a hazard ratio of 1.05 (95% CI, .64–1.74; P = .831). Conclusions: HCV reinfection remains a frequent finding among MSM in Germany. In addition to behavioral interventions, early HCV treatment and retreatment should be implemented for this subgroup to prevent HCV transmission. Abstract : The hepatitis C virus reinfection rate in men who have sex with men remains consistently high in the direct-acting antivirals era, compared to the interferon era. Micro-elimination strategies need to adapt to this finding.